Emancipation of the look: the role of photography in a reflective school formationv (Olhar de Professor, 2022)
This article discusses questions about photography as a driver of critical thinking and the formation of reflective subjects in contemporary society. To this end, photography is situated as a source of communication, being considered a non-verbal language (FERRARA, 2002), resulting from a perception of reality (DUBOIS, 1993) and a poetic creation of the imaginary (DURAND, 2004). The work analyzes activities developed in the extension project “PhotoGraphein vai à Escola” (UFPel), with elementary school students in public schools in the region of Pelotas and Rio Grande - RS. The extension activities work based on forming aesthetic experiences (DEWEY, 2010) and the relationship between photography and the look, making it possible to envision how much such issues reverberate within the scope of teaching in Visual Arts. With this analysis, it was possible to perceive established relationships and learning that positively altered the way that young students decode and perceive the symbols present in the world around them, enabling the transformation of the lived into forming experiences for all involved.
Keywords: Visual Arts. Education. Photography. Experience. Basic education.